Yeosin-san Increases Female Fertility through Inducing Uterine Receptivity and Ovarian Function - Choi, Hee Jung; Joo, Bo Sun; Park, Mi Ju; Park, Min Jung; Bae, Boram; Kim, Bo Sung; Park, Hye Rin; Kim, Keuk Jun; Yang, Hee Jin; Yoo, Jeong Eun; Chung, Tae Wook; Joo, Jongkil; et al. (Journal of Physiology & Pathology in Korean Medicine, 2019)
Despite the development of assisted reproduction technologies (ART) including in vitro fertilization (IVF), the poor ovarian response and endometrial receptivity remains clinically a major unmet need. Although these problems are difficulties to solve in infertility treatment, there are no good therapeutic option yet. Traditional herbal remedies and acupuncture, therefore are being proposed as alternative treatment. Our group found that traditional herbal medicines such as Paeonia lactiflora L.(PL, 芍藥), Cyperus rotundus L.(CR, 香附子), and Perilla frutescens (PF, 紫蘇葉) could improve endometrial receptivity. In this study, we found out Yeosin-san (如神散) as an optimal herbal formula via combination of the previously established herbal medicines. Yeosin-san is a traditional Korean medical formula which was established by Ziming Jin (陳自明) and recorded in Furendaiquanliangfang (婦人大全良方) at first. The formula traditionally used for treating abnormal uterine bleeding and leukorrhea. It showed a highest effect on leukemia inhibitory factor (LIF) expression and on the adhesion between trophoblastic cells and endometrial cells. In addition, it has been shown that the Yeosin-san not only increases the endometrial receptivity to improve the embryo implantation but also enhances the ovary function by expressing the angiogenesis-related genes. Here we suggest that Yeosin-san could be a novel and effective candidate for treating female infertility. KCI Citation Count: 0